Bortezomib‐induced peripheral neuropathy: A genome‐wide association study on multiple myeloma patients. Issue 1 (20th March 2017) - Campo, Chiara; da Silva Filho, Miguel Inacio; Weinhold, Niels; Mahmoudpour, Seyed Hamidreza; Goldschmidt, Hartmut; Hemminki, Kari; Merz, Maximilian; Försti, Asta
Abstract: The proteasome‐inhibitor bortezomib was introduced into the treatment of multiple myeloma more than a decade ago. It is clinically beneficial, but peripheral neuropathy (PNP) is a side effect that may limit its use in some patients. To examine the possible genetic predisposing factors to PNP, we performed a genome‐wide association study on 646 bortezomib‐treated German multiple myeloma patients. Our aim was to identify genetic risk variants associated with the development of PNP as a serious side effect of the treatment. We identified 4 new promising loci for bortezomib‐induced PNP at 4q34.3 (rs6552496), 5q14.1 (rs12521798), 16q23.3 (rs8060632), and 18q21.2 (rs17748074). Even though the results did not reach genome‐wide significance level, they support the idea of previous studies, suggesting a genetic basis for neurotoxicity. The identified single nucleotide polymorphisms map to genes or next to genes involved in the development and function of the nervous system ( CDH13, DCC, and TENM3 ). As possible functional clues, 2 of the variants, rs12521798 and rs17748074, affect enhancer histone marks in the brain. The rs12521798 may also impact expression of THBS4, which affects specific signal trasduction pathways in the nervous system. Further research is needed to clarify the mechanism of action of the identified single nucleotide polymorphisms in the development of drug‐induced PNP and to functionally validate our in silico predictions.